2018
DOI: 10.3390/app8112077
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Transfer and Thermal Environment in a Rural Residential Building for Addressing Energy Poverty

Abstract: Reducing energy consumption and creating a comfortable thermal indoor environment in rural residential buildings can play a key role in fighting global warming in China. As a result of economic development, rural residents are building new houses and modernizing existing buildings. This paper investigated and analyzed a typical rural residential building in the Ningxia Hui Autonomous Region in Northwest China through field measurements and numerical simulation. The results showed that making full use of solar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In refurbishment processes, PCM boards can be added to walls, without changing considerably the existing design, while in new constructions several options are available, namely by encapsulating these materials in the building elements [30,32]. PCMs have unique properties that allow them to increase the thermal inertia of buildings without increasing the weight of the structures [32,33].…”
Section: Evolution Of Constructive Solutions and Thermal Comfortmentioning
confidence: 99%
“…In refurbishment processes, PCM boards can be added to walls, without changing considerably the existing design, while in new constructions several options are available, namely by encapsulating these materials in the building elements [30,32]. PCMs have unique properties that allow them to increase the thermal inertia of buildings without increasing the weight of the structures [32,33].…”
Section: Evolution Of Constructive Solutions and Thermal Comfortmentioning
confidence: 99%
“…The field measurements and numerical simulation was carried out by Zhu et al [9] to assess the energy performance of a typical rural residential building in the Ningxia Hui Autonomous Region in Northwest China. It was found that application of solar energy resources is an effective approach to improve the indoor temperature.…”
Section: Sustainable Energy Systems Planning Integration and Managementioning
confidence: 99%
“…In addition, there is an ongoing debate about the type of social aid in both academic society (see References Karásek and Pojar [60], Oppenheim [61], Scarpellini et al [62]) and social/political campaigns (for instance, see References Thomson and Bouzarovski [22], Enet English [37], Daily Mail Press Association [63], Long-Bailey [64]). Three other popular strategies to alleviate energy poverty are to "increase energy efficiency of dwelling" [65,66], "increase energy affordability and demand management" [61,67,68] and "increase access to clean/modern energy" [69][70][71]. The first two strategies are more common in developed regions (regions with high access to clean/modern energy), while the third one is the policy in less developed regions.…”
Section: Category Indicator Country/region Applied Tomentioning
confidence: 99%